Self-care practices and immediate side effects in women with gynecological cancer in brachytherapy - Rosimeri Helena da Silva; Luciana Martins da Rosa; Mirella Dias; Nádia Chiodelli Salum; Ana Inêz Severo Varela; Vera Radünz (Universidade Federal de Santa Maria, 2021)
Objective: to reveal the immediate side effects and self-care practices adopted by women with gynecological cancer submitted to brachytherapy. Method: narrative research, conducted with 12 women, in southern Brazil, between December/2018 and January/2019, including semi-structured interviews submitted to content analysis. Results: three thematic categories emerged from the analysis: Care oriented and adopted by women in pelvic brachytherapy; Immediate side effects perceived by women in pelvic brachytherapy; Care not guided by health professionals. The care provided by the nurses most reported by the women was vaginal dilation, use of a shower and vaginal lubricant, tea consumption, cleaning, and storage of the vaginal dilator. The side effects most frequently mentioned in the interviews were urinary and intestinal changes in the skin and mucous membranes. Conclusion: nursing care in brachytherapy must prioritize care to prevent and control genitourinary and cutaneous changes, including self-care practices.